Iron oxide-cerium oxide composite material and preparation method and application thereof

By using the "egg yolk-egg shell" structure nanoreactor of iron oxide-cerium oxide composite in lithium sulfur batteries, the problems of insufficient conductivity and slow conversion reaction kinetics in lithium sulfur batteries are solved, and the battery performance improvement and commercial production possibility is achieved.

CN119549155AActive Publication Date: 2025-03-04GUANGDONG UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411452489.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-04
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

Lithium-sulfur batteries have problems such as insufficient conductivity, volume expansion, slow polysulfide shuttle behavior and conversion reaction kinetics, resulting in low utilization of active substances, low Coulomb efficiency and rapid decline in battery capacity.

Method used

Using a preparation method of an iron oxide-cerium oxide composite material, a nanoreactor with an "egg yolk-egg shell" structure is formed by compositeing the iron oxide with the cerium oxide to form a nanoreactor with a "egg yolk-egg shell" structure, thereby enhancing the reactivity and selectivity of the catalyst.

Benefits of technology

The synergistic catalytic performance of catalysts in lithium-sulfur batteries is achieved, the rate performance and overall performance of the battery are improved, and the cycle stability and energy density of the battery are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549155A_ABST
    Figure CN119549155A_ABST
Patent Text Reader

Abstract

The invention relates to an iron oxide-cerium oxide composite material and a preparation method and application thereof.The preparation method comprises the steps that etched Fe3O4 (at) C is coated with rare earth elements in an alkaline environment, and cerium oxide distribution sites are prepared by controlling the difference of reaction steps; the invention also discloses an iron oxide-cerium oxide composite material with a yolk-eggshell nano-structure with an excellent heterojunction tandem catalytic interface and an iron oxide-cerium oxide composite material with a yolk-eggshell nano-structure. The rare earth element Ce with an electron-rich 4f internal valence orbit is utilized, f orbit electron spinning causes increase of electronic states near dxz / yz, a pi bond formed by dxz / yz and px / y hybridization is enhanced, d-p hybridization is promoted, and the d orbit and the p orbit are overlapped to the maximum when interacting with LiPSs. When the composite material is applied to lithium-sulfur batteries, f-d-p orbits are coupled and interact with LiPSs, f-d-p hybridization is generated, 4f orbits are activated, catalytic action is exerted, and reaction activity is improved, so that the composite material has high reversible capacity, good rate capability, long cycle life and competitive area capacity under high-sulfur load when being applied to the lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-sulfur batteries, and in particular to an iron oxide-cerium oxide composite material and a preparation method and application thereof. Background Art

[0002] Achieving the vision of "carbon neutrality" poses new and severe challenges to the efficient collection, storage, conversion and use of energy. Over the past three decades, lithium-ion batteries have played a core role in promoting innovations in areas such as portable electronic devices and electric vehicles. However, the limitations of their energy density have become increasingly prominent, making it difficult to meet the urgent needs of today's rapidly developing society. Lithium-sulfur batteries are considered to be the most practical candidate for the next generation of high-performance secondary batteries due to their excellent theoretical energy density, abundant sulfur resource reserves, and green environmental protection.

[0003] Although lithium-sulfur batteries show broad application prospects, their practical application still faces challenges. Specifically, the problems with the sulfur positive electrode include insufficient conductivity, significant volume expansion, "shuttle" behavior of polysulfides, and slow conversion reaction kinetics, which together lead to a decrease in the effective utilization of active materials, low Coulomb efficiency, and rapid decline in battery capacity. In addition, the growth of lithium dendrites at the negative electrode also poses serious safety risks to the battery.

[0004] Current research on catalysts focuses on optimizing energy levels to promote the adsorption and catalytic conversion of LiPSs, often ignoring the effects of electron spin states on charge transfer and orbital interactions. Catalytic performance is affected by factors such as the electronic structure, orbital structure, atomic diameter, and loading of the central atom. Most single-atom catalysts are composed of 3d, 4d, 5d, and p-block metals.

[0005] The iron oxide-cerium oxide composite has a "yolk-eggshell" structure nanoreactor with an iron oxide core and a conductive carbon shell. The core-shell structure, in which the adsorption capacity of LiPSs decreases from the inside to the outside, is more effective in limiting the diffusion of polysulfides and regulating the deposition of LiPSs.

[0006] Therefore, there is an urgent need to develop a method for preparing an iron oxide-cerium oxide composite material with high product purity, utilizing the unique electronic structure, 4f valence orbital and unsaturated coordination environment of rare earth (RE) elements, as well as a "yolk-eggshell" nanoreactor, to enhance the reaction activity and selectivity of the catalyst to realize commercial lithium-sulfur batteries. Summary of the invention

[0007] Based on this, the purpose of the present invention is to provide a method for preparing an iron oxide-cerium oxide composite material. The preparation method has simple steps and mild conditions. The iron oxide-cerium oxide composite materials with different morphologies and crystal structures can be obtained by precisely controlling the reaction conditions, and the target product is evenly dispersed and has a regular morphology.

[0008] Another object of the present invention is to provide an iron oxide-cerium oxide composite material, which is uniformly dispersed, has a regular core-shell structure morphology, exhibits excellent electrochemical properties, can be well applied to lithium-sulfur batteries; and has obvious interface effects, and the catalyst exhibits synergistic catalytic performance in lithium-sulfur batteries.

[0009] Another object of the present invention is to provide an application of an iron oxide-cerium oxide composite material in a lithium-sulfur battery.

[0010] The inventors of the present application have discovered that the use of iron oxide and cerium oxide to form an iron oxide-cerium oxide composite for catalytic reactions in lithium-sulfur batteries can produce a synergistic catalytic effect and enhance reaction activity. Therefore, the present invention aims to develop a method for commercially producing iron oxide-cerium oxide composites that has a simple preparation process, low cost, and excellent product performance.

[0011] The present invention adopts the following technical solution:

[0012] A method for preparing an iron oxide-cerium oxide composite material comprises the following steps:

[0013] S1: Dissolve soluble iron salt in ultrapure water and then adjust the pH value;

[0014] S2: placing the solution obtained in step S1 in a reaction kettle, subjecting it to high temperature reaction, centrifugally washing and drying it;

[0015] S3: dissolving the product of step S2 in a weak alkaline solution, adding dopamine hydrochloride solution, stirring, centrifuging, washing and drying;

[0016] S4: calcining the product of step S3 at high temperature to obtain an intermediate product I;

[0017] S5: dissolving an inorganic acid in ultrapure water, adding the intermediate product I, stirring, centrifuging, washing and drying to obtain an intermediate product II;

[0018] S6: dispersing the intermediate product II, the cerium salt and the alkaline solution in a mixed solvent of ultrapure water and ethanol, and reacting the solution to obtain a mixed solution;

[0019] S7: After the mixed solution is transferred into a reaction container, reacted at 100-400° C., centrifuged, washed and dried to obtain a near-final product;

[0020] S8: The final product is placed in a tube furnace and calcined at 350-600°C for 2-4 hours.

[0021] The present invention provides a method for preparing an iron oxide-cerium oxide composite material, which can obtain iron oxide-cerium oxide composite materials with different morphologies and crystal structures by precisely controlling the reaction conditions in each step, and highlighting different properties. The preparation process is simple to operate, the experimental reproducibility is very good, the cost is low, and the iron oxide-cerium oxide composite material is easy to mass produce. In addition, the iron oxide-cerium oxide composite material prepared by the method has obvious interface effects, and as a catalyst, it exhibits synergistic catalytic performance in lithium-sulfur batteries.

[0022] Furthermore, the soluble iron salt in step S1 is selected from one or more of ferric chloride, ferric nitrate and ferric sulfate.

[0023] Furthermore, in step S1, the pH value is adjusted by using an inorganic base.

[0024] Furthermore, by controlling different pH values ​​in step S1, products with different morphologies can be obtained after the high temperature reaction in step S2.

[0025] Specifically, in step S1, the pH is adjusted within the range of 8≤pH≤10, and the product obtained in step S2 has a cubic morphology; in step S1, the pH is adjusted within the range of 10<pH≤13, and the product obtained in step S2 has a peanut-like morphology.

[0026] Furthermore, in step S2, the high temperature reaction conditions are: reacting at 100-130°C in a reactor for 36-60h; and Fe2O3 is obtained after the reaction is completed.

[0027] Furthermore, in step S3, the weak base solution is one or more of tris(hydroxymethyl)aminomethane (Tris), tris(hydroxymethyl)aminoethane, aminoacetic acid, diaminoacetic acid, 4-aminobenzoic acid, amino acid buffer, and N-hydroxyethylpiperazine-N'-ethanesulfonic acid.

[0028] Furthermore, in step S4, the product obtained in step S3 is calcined in a high temperature furnace at 550-700°C for 2h, and the obtained intermediate product I is Fe3O4@C.

[0029] Furthermore, the inorganic acid in step S5 is one or more of hydrochloric acid, sulfuric acid, and nitric acid, preferably hydrochloric acid.

[0030] Furthermore, in step S5, the intermediate product II obtained by inorganic acid etching is a hollow Fe3O4@C cubic structure.

[0031] Furthermore, the alkaline solution in step S6 is selected from one or more of urea, sodium hydroxide, potassium hydroxide, ammonia water, and hexamethylenetetramine. Preferably, the alkaline solution is hexamethylenetetramine.

[0032] Furthermore, in step S6, the solution may be dispersed by stirring or by ultrasonic dispersion.

[0033] Specifically, the alkaline solution is hexamethylenetetramine, cerium salt is added and stirred and dispersed, the iron oxide-cerium oxide composite material is a "yolk-eggshell" type structure, and CeO2 grows in nanosheets on the surface and core of Fe3O4. The nanosheet-like cerium oxide structure provides a larger specific surface area, which helps the rapid diffusion and reaction of lithium ions and improves the rate performance of the battery. Due to the superposition of the nanosheets, a good conductive network is formed, which can effectively improve the current transmission efficiency.

[0034] Specifically, the alkaline solution is hexamethylenetetramine, cerium salt is added for ultrasonic dispersion, the iron oxide-cerium oxide composite material is a "yolk-eggshell" structure, and CeO2 is nanoparticles grown on the surface and in the core of Fe3O4. CeO2 nanoparticles doped with carbon nanoboxes can spatially confine and chemically capture LiPSs to reduce the shuttle effect, and have good dispersion, which is conducive to improving the uniformity of the composite material and enhancing the overall performance of the battery.

[0035] Furthermore, the cerium salt in step S6 is selected from one or more of cerium chloride, cerium nitrate, cerium acetate, and cerium sulfate.

[0036] Furthermore, the intermediate product II in step S6 is a hollow structure containing Fe3O4; in step S6, the structure and morphology of the reaction product can be controlled by adjusting the molar ratio of Fe3O4 to the cerium salt.

[0037] Specifically, the molar ratio of Fe3O4 to cerium salt is (1-20):1, and an iron oxide-cerium oxide composite material with differentiated cerium oxide distribution sites is obtained. The molar ratio of Fe3O4 to cerium salt is 1:(2-20), and Ce is controlled to penetrate into the egg yolk Fe3O4 structure, and after subsequent calcination, a Fe3O4-CeO2@C or Fe2O3-Ce2O3@C tandem catalytic heterojunction is obtained.

[0038] Furthermore, in step S6, the ratio of ultrapure water to ethanol mixed solvent is (1-5):1, so as to control the size of CeO2 particles and the uniform distribution of CeO2 in the Fe3O4@C iron oxide-cerium oxide composite material.

[0039] Furthermore, in step S7, the product structure can be further controlled by controlling the reaction temperature of the hydrothermal reaction.

[0040] Specifically, a hydrothermal reaction is carried out at 200-300°C to form an ordered structure, which grows into a nanorod in contact with a nanocore. The introduction of cerium regulates the growth of the crystal, improves the dispersion and uniformity of the material, and increases the reaction activity.

[0041] Specifically, a hydrothermal reaction is carried out at 301-400° C. to form an elliptical shape in contact with the nanocore, causing a partial mutual reaction, resulting in a tighter bond and enhancing the stability and catalytic performance of the material.

[0042] Furthermore, in step S8, the calcination temperature is controlled to control the crystal structure of the product.

[0043] Specifically, when the calcination temperature is 350°C≤≤450°C, the iron oxide is Fe3O4 and the cerium oxide is CeO2. When the calcination temperature is 450°C<≤600°C, Fe3O4 becomes α-Fe2O3, the morphology changes from nanoparticles to porous, CeO2 becomes Ce2O3, and the particle size can be precisely controlled by the reaction conditions.

[0044] The beneficial effects of the present invention are:

[0045] (1) The purpose of the present invention is to solve the problems of low capacity and poor cycle stability of current lithium-sulfur batteries, and accordingly propose a new process for preparing a composite material of iron oxide-cerium oxide with a "yolk-eggshell" structure. By compounding iron oxide with cerium oxide, cerium is a rare earth element, 4f x 5d y 6s valence electron configuration, fdp orbital coupling, generates fdp hybridization when interacting with LiPSs, activates closed and inactive 4f orbitals, and provides abundant channels and space for ion diffusion and electrolyte flow; special valence electron structure and large atomic radius form a higher coordination number, produce strong substrate anchoring effect and a wider range of electron delocalization effect. The 4f orbital properties of the rare earth valence layer (high degeneracy and locality) provide richer spin-orbit coupling than d orbitals. Rare earth and coordinated atoms form a local "electron transfer bridge" or "electron storage station" through rich spin-orbit coupling, activating adsorbates to promote subsequent catalytic conversion reactions.

[0046] (2) The preparation method of the present invention is simple. It uses inorganic acid to etch Fe3O4@C, accurately controls the reaction rate and internal core of the synthesis process, designs a "yolk-eggshell" structure with a LiPSs adsorption gradient, increases the area / volume load of sulfur, reduces the usage rate of the electrolyte, and increases the sulfur utilization rate, so as to further improve the volume energy / power density of the Li-S battery.

[0047] (3) The iron oxide-cerium oxide composite material was successfully prepared by a simple hydrothermal synthesis method and post-calcination. The entire preparation process is simple to operate, environmentally friendly, has very good experimental reproducibility, is low in cost, and is easy to commercialize for lithium-sulfur batteries. The iron oxide-cerium oxide composite material can be mass-produced.

[0048] (4) The "yolk-eggshell" nanoreactor prepared by the present invention uses a "cavity" structure combined with the cerium element as an active center container to provide a volume buffer cavity; the "yolk" active center is designed to improve catalytic conversion and accelerate reaction kinetics; the microenvironment formed by flexible active sites and rich molecular diffusion paths regulates the conversion of sulfur substances within a specific nanoscale range, providing rich channels and space for ion diffusion and electrolyte flow.

[0049] (5) The cerium oxide nanostructure of the present invention is closely grown on the surface of the iron oxide, forming a rich nano-interface to ensure strong chemical interaction between metals.

[0050] (6) The iron oxide-cerium oxide composite material prepared by the present invention can be well applied to lithium-sulfur batteries. It has obvious interfacial effect and exhibits synergistic catalytic performance as a catalyst in lithium-sulfur batteries.

[0051] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is the XRD pattern of the iron oxide-cerium oxide composite material prepared in Example 1;

[0053] Figure 2-a This is a TEM image of the iron oxide-cerium oxide composite material prepared in Example 1;

[0054] Figure 2-b This is a TEM image of the iron oxide-cerium oxide composite material prepared in Example 2;

[0055] Figure 2-c This is a TEM image of the iron oxide-cerium oxide composite material prepared in Example 3;

[0056] Figure 3 This is a SEM image of the iron oxide-cerium oxide composite material prepared in Example 1;

[0057] Figure 4-a This is a performance diagram of the iron oxide-cerium oxide composite material prepared in Example 1-2 at 0.5C;

[0058] Figure 4-bThis is a performance diagram of the iron oxide-cerium oxide composite material prepared in Example 1-2 at 1C;

[0059] Figure 5-a This is a performance diagram of the iron oxide-cerium oxide composite material prepared in Example 3-5 at 0.5C;

[0060] Figure 5-b This is a performance diagram of the iron oxide-cerium oxide composite material prepared in Examples 3-5 at 1C. DETAILED DESCRIPTION

[0061] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] A method for preparing an iron oxide-cerium oxide composite material comprises the following steps:

[0063] S1: Dissolve soluble iron salt in ultrapure water and then adjust the pH value;

[0064] S2: placing the solution obtained in step S1 in a reaction kettle, and reacting it at 100-130° C. for 36-60 hours in the reaction kettle; after the reaction, Fe2O3 is obtained, and then centrifuged, washed and dried;

[0065] S3: dissolving the product of step S2 in a weak alkaline solution, adding dopamine hydrochloride solution, stirring, centrifuging, washing and drying;

[0066] S4: calcining the product of step S3 in a high temperature furnace at 550-700°C for 2h to obtain an intermediate product I of Fe3O4@C;

[0067] S5: dissolving the inorganic acid in ultrapure water, adding the intermediate product I, stirring, centrifuging, washing and drying to obtain the intermediate product II, which is YS Fe3O4@C;

[0068] S6: weighing the intermediate product II, the cerium salt and the hexamethylenetetramine in proportion in a mixed solvent of ultrapure water and ethanol, stirring or ultrasonically dispersing the solution uniformly and reacting to obtain a mixed solution;

[0069] S7: After the mixed solution is transferred into a reactor, reacted at 100-400° C., washed by centrifugation with water and ethanol and dried to obtain a near-final product;

[0070] S8: placing the nearly final product in a tubular furnace and calcining at 400-600° C. for 2-4 hours to obtain the target product, an iron oxide-cerium oxide composite material catalyst.

[0071] Example 1

[0072] 30mL of ultrapure water was added to the inner tank, heated to 75°C in a water bath, 16.218g of FeCl3·6H2O was weighed, added to the inner tank, and stirred for 5min to obtain solution A. A certain amount of NaOH was weighed and dissolved in ultrapure water to obtain solution B. Solution B was poured into solution A to adjust the pH to 8.25. The obtained solution was transferred to a reactor and reacted at 110°C for 48h. After the reaction, the sample was collected, washed with water 2-3 times, washed with ethanol 2-3 times, and dried to obtain Fe2O3. 1g of Fe2O3 and 0.1214g of Tris were dissolved in 100mL of ultrapure water to form solution C. 0.6g of dopamine hydrochloride was dissolved in 12mL of ultrapure water to form solution D. Solution D was poured into solution C, stirred at room temperature for 12h, centrifuged and washed, and dried. Calcine at 600℃ for 2h in a tube furnace. After the reaction is completed, collect the sample to obtain Fe3O4@C. Drop hydrochloric acid into ultrapure water, add the material, and etch for 4h at room temperature to obtain YS Fe3O4@C. Weigh 100mg YS Fe3O4@C, 60mg Ce(NO)3·6H2O and 8mg hexamethylenetetramine and stir and disperse them in a mixed solvent of 30mL ultrapure water and 30mL ethanol. Transfer the obtained solution to a reactor and react at 100℃ for 10h. After the reaction is completed, collect the sample, wash it with water 2-3 times, wash it with ethanol 2-3 times, and dry it. Calcine at 400℃ for 3h in a tube furnace to obtain the target product, iron oxide-cerium oxide composite catalyst.

[0073] Example 2

[0074] 30 mL of ultrapure water was added to the inner tank, heated to 75 ° C in a water bath, 16.218 g of FeCl3·6H2O was weighed, added to the inner tank, and stirred for 5 min to obtain solution A. A certain amount of NaOH was weighed and dissolved in ultrapure water to obtain solution B. Solution B was poured into solution A to adjust the pH to 8.25. The obtained solution was transferred to the reactor and reacted at 110 ° C for 48 h. After the reaction, the sample was collected, washed with water 2-3 times, washed with ethanol 2-3 times, and dried to obtain Fe2O3. 1 g of Fe2O3 and 0.1214 g of Tris were dissolved in 100 mL of ultrapure water to form solution C. 0.6 g of dopamine hydrochloride was dissolved in 12 mL of ultrapure water to form solution D. Solution D was poured into solution C, stirred at room temperature for 12 h, centrifuged and washed, and dried. Calcine at 600℃ for 2h in a tube furnace. After the reaction is completed, collect the sample to obtain Fe3O4@C. Drop hydrochloric acid into ultrapure water, add the material, and etch for 4h at room temperature to obtain YS Fe3O4@C. Weigh 100mg YSFe3O4@C, 60mg Ce(NO)3·6H2O and 8mg hexamethylenetetramine and ultrasonically disperse them in a mixed solvent of 30mL ultrapure water and 30mL ethanol. Transfer the obtained solution to a reactor and react at 100℃ for 10h. After the reaction is completed, collect the sample, wash it with water 2-3 times, wash it with ethanol 2-3 times, and dry it. Calcine at 400℃ for 3h in a tube furnace to obtain the target product, iron oxide-cerium oxide composite catalyst.

[0075] Example 3

[0076] 30 mL of ultrapure water was added to the inner tank, heated to 75 ° C in a water bath, 16.218 g of FeCl3·6H2O was weighed, added to the inner tank, and stirred for 5 min to obtain solution A. A certain amount of NaOH was weighed and dissolved in ultrapure water to obtain solution B. Solution B was poured into solution A to adjust the pH to 12. The obtained solution was transferred to the reactor and reacted at 110 ° C for 48 h. After the reaction, the sample was collected, washed with water 2-3 times, washed with ethanol 2-3 times, and dried to obtain Fe2O3. 1 g of Fe2O3 and 0.1214 g of Tris were dissolved in 100 mL of ultrapure water to form solution C. 0.6 g of dopamine hydrochloride was dissolved in 12 mL of ultrapure water to form solution D. Solution D was poured into solution C, stirred at room temperature for 12 h, centrifuged and washed, and dried. Calcinate at 600℃ in a tube furnace for 2h. After the reaction is completed, collect the sample to obtain Fe3O4@C. Drop hydrochloric acid into ultrapure water, add the material, and etch for 4h at room temperature to obtain YS Fe3O4@C. Weigh 100mg YSFe3O4@C, 44mg Ce(NO)3·6H2O and 8mg hexamethylenetetramine and stir and disperse them in a mixed solvent of 30mL ultrapure water and 30mL ethanol. Transfer the obtained solution to a reactor and react at 100℃ for 10h. After the reaction is completed, collect the sample, wash it with water 2-3 times, wash it with ethanol 2-3 times, and dry it. Calcinate at 400℃ in a tube furnace for 3h to obtain the target product, iron oxide-cerium oxide composite catalyst.

[0077] Example 4

[0078] 30 mL of ultrapure water was added to the inner tank, heated to 75 ° C in a water bath, 16.218 g of FeCl3·6H2O was weighed, added to the inner tank, and stirred for 5 min to obtain solution A. A certain amount of NaOH was weighed and dissolved in ultrapure water to obtain solution B. Solution B was poured into solution A to adjust the pH to 8.25. The obtained solution was transferred to the reactor and reacted at 110 ° C for 48 h. After the reaction, the sample was collected, washed with water 2-3 times, washed with ethanol 2-3 times, and dried to obtain Fe2O3. 1 g of Fe2O3 and 0.1214 g of Tris were dissolved in 100 mL of ultrapure water to form solution C. 0.6 g of dopamine hydrochloride was dissolved in 12 mL of ultrapure water to form solution D. Solution D was poured into solution C, stirred at room temperature for 12 h, centrifuged and washed, and dried. Calcine at 600℃ for 2h in a tube furnace. After the reaction is completed, collect the sample to obtain Fe3O4@C. Drop hydrochloric acid into ultrapure water, add the material, and etch for 4h at room temperature to obtain YS Fe3O4@C. Weigh 100mg YSFe3O4@C, 80mg Ce(NO)3·6H2O and 8mg hexamethylenetetramine and stir and disperse them in a mixed solvent of 30mL ultrapure water and 30mL ethanol. Transfer the obtained solution to a reactor and react at 100℃ for 10h. After the reaction is completed, collect the sample, wash it with water 2-3 times, wash it with ethanol 2-3 times, and dry it. Calcine at 400℃ for 3h in a tube furnace to obtain the target product, iron oxide-cerium oxide composite catalyst.

[0079] Example 5

[0080] 30 mL of ultrapure water was added to the inner tank, heated to 75 ° C in a water bath, 16.218 g of FeCl3·6H2O was weighed, added to the inner tank, and stirred for 5 min to obtain solution A. A certain amount of NaOH was weighed and dissolved in ultrapure water to obtain solution B. Solution B was poured into solution A to adjust the pH to 8.25. The obtained solution was transferred to the reactor and reacted at 110 ° C for 48 h. After the reaction, the sample was collected, washed with water 2-3 times, washed with ethanol 2-3 times, and dried to obtain Fe2O3. 1 g of Fe2O3 and 0.1214 g of Tris were dissolved in 100 mL of ultrapure water to form solution C. 0.6 g of dopamine hydrochloride was dissolved in 12 mL of ultrapure water to form solution D. Solution D was poured into solution C, stirred at room temperature for 12 h, centrifuged and washed, and dried. Calcine at 600℃ for 2h in a tube furnace. After the reaction is completed, collect the sample to obtain Fe3O4@C. Drop hydrochloric acid into ultrapure water, add the material, and etch for 4h at room temperature to obtain YS Fe3O4@C. Weigh 100mg YSFe3O4@C, 120mg Ce(NO)3·6H2O and 8mg hexamethylenetetramine and stir and disperse them in a mixed solvent of 30mL ultrapure water and 30mL ethanol. Transfer the obtained solution to a reactor and react at 100℃ for 10h. After the reaction is completed, collect the sample, wash it with water 2-3 times, wash it with ethanol 2-3 times, and dry it. Calcine at 400℃ for 3h in a tube furnace to obtain the target product, iron oxide-cerium oxide composite catalyst.

[0081] Performance Testing

[0082] The iron oxide-cerium oxide composite catalyst prepared in Examples 1-5 was subjected to the following performance tests: 1. XRD test

[0083] Figure 1 This is an XRD test of the iron oxide-cerium oxide composite material prepared in Example 1. The results show that the sample is a composite of Fe3O4 (JCPDS19-0629) and CeO2 (JCPDS 43-1002).

[0084] 2. TEM test

[0085] FIG2 is a TEM image of the iron oxide-cerium oxide composite material prepared in Examples 1-3. From the figure, it can be seen that Examples 1-3 all prepared yolk-eggshell core-shell structure Fe3O4-CeO2 composite materials with a size of about 500 nm.

[0086] Among them from Figure 2-a It can be seen that the Fe3O4-CeO2 composite material obtained by stirring and dispersing in Example 1 has a cubic core-shell structure, and CeO2 grows in the form of nanosheets on the surface of Fe3O4 and in the core. Figure 2-bIt can be seen that the Fe3O4-CeO2 composite material obtained by ultrasonic dispersion in Example 2 has a cubic core-shell structure, and CeO2 is nanoparticles grown on the surface of Fe3O4 and in the core. Figure 2-c It can be seen that in Example 3, the pH value of the soluble iron salt solution was adjusted to 12 to obtain a peanut-shaped Fe3O4-CeO2 composite material.

[0087] 3. SEM test

[0088] Figure 3 This is a SEM image of the Fe3O4-CeO2 composite material prepared in Example 1. From the SEM image, it can be seen that the synthesized Fe3O4-CeO2 composite material has a cubic box structure with a size of about 500nm.

[0089] 4. Battery performance test

[0090] Figure 4 is a performance test diagram of the iron oxide-cerium oxide composite material prepared in Example 1 and Example 2 at 0.5C and 1C. It can be seen from the figure that the iron oxide-cerium oxide composite material obtained by stirring and dispersing and the iron oxide-cerium oxide composite material obtained by ultrasonic dispersion can both exhibit excellent electrocatalytic performance. The CeO2 in Example 1 is a nanosheet grown on the surface and core of Fe3O4. The nanosheet-like CeO2 structure provides a large specific surface area, which is conducive to the rapid diffusion and reaction of lithium ions and improves the rate performance of the battery. Due to the superposition between the nanosheets, a good conductive network is formed, which can effectively improve the current transmission efficiency. In Example 2, CeO2 is a nanoparticle grown on the surface and core of Fe3O4. CeO2 nanoparticles doped with carbon nanoboxes can spatially confine and chemically capture LiPSs to reduce the shuttle effect, and have good dispersibility, which is conducive to improving the uniformity of the composite material and enhancing the overall performance of the battery.

[0091] Figure 5 is a performance test diagram of the iron oxide-cerium oxide composite material prepared in Example 3-5 at 0.5C and 1C. It can be seen that the iron oxide-cerium oxide composite material with excellent electrocatalytic performance can be prepared within a certain range of the molar ratio of Fe3O4 to cerium salt.

[0092] It can be seen that the present invention can obtain composite materials with different morphologies and crystal structures by controlling the reaction conditions, and the "yolk-eggshell" nanoreactor obtained by compounding iron oxide with cerium oxide, through the "cavity" structure combined with the cerium element, is used as an active center container to provide a volume buffer cavity; the "yolk" active center is designed to improve catalytic conversion and accelerate reaction kinetics. The microenvironment formed by flexible active sites and rich molecular diffusion paths regulates the conversion of sulfur substances within a specific nanoscale range, providing rich channels and spaces for ion diffusion and electrolyte flow.

[0093] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A method for preparing an iron oxide-cerium oxide composite material, characterized in that: The following steps are involved: S1: Dissolve soluble iron salt in ultrapure water and then adjust the pH value; S2: placing the solution obtained in step S1 in a reaction kettle, subjecting it to high temperature reaction, centrifugally washing and drying it; S3: dissolving the product of step S2 in a weak alkaline solution, adding dopamine hydrochloride solution, stirring, centrifuging, washing and drying; S4: calcining the product of step S3 at high temperature to obtain an intermediate product I; S5: dissolving an inorganic acid in ultrapure water, adding the intermediate product I, stirring, centrifuging, washing and drying to obtain an intermediate product II; S6: dispersing the intermediate product II, the cerium salt and the selected alkaline solution in a mixed solvent of ultrapure water and ethanol, and reacting the solution to obtain a mixed solution; S7: After the mixed solution is transferred into a reaction container, reacted at 100-400° C., centrifuged, washed and dried to obtain a near-final product; S8: placing the nearly final product in a tube furnace and calcining it at 350-600° C. for 2-4 hours to obtain an iron oxide-cerium oxide composite material.

2. The method for preparing an iron oxide-cerium oxide composite material according to claim 1, characterized in that: The soluble iron salt in step S1 is selected from one or more of ferric chloride, ferric nitrate and ferric sulfate.

3. The method for preparing an iron oxide-cerium oxide composite material according to claim 1, characterized in that: In step S1, the pH range is adjusted to 8≤pH≤10, and the product obtained in step S2 has a cubic morphology; Alternatively, in step S1, the pH range is adjusted to 10<pH≤13, and the product obtained in step S2 has a peanut-like morphology.

4. The method for preparing an iron oxide-cerium oxide composite material according to claim 1, characterized in that: The cerium salt in step S6 is selected from one or more of cerium chloride, cerium nitrate, cerium acetate, and cerium sulfate.

5. The method for preparing an iron oxide-cerium oxide composite material according to claim 1, characterized in that: The alkaline solution in step S6 is selected from one or more of urea, sodium hydroxide, potassium hydroxide, ammonia water, and hexamethylenetetramine.

6. The method for preparing an iron oxide-cerium oxide composite material according to claim 1, characterized in that: The dispersion method in step S6 is a stirring method or an ultrasonic method.

7. The method for preparing an iron oxide-cerium oxide composite material according to claim 1, characterized in that: The intermediate product II described in step S6 is a hollow structure containing Fe3O4; The molar ratio of Fe3O4 to cerium salt is (1-20):1; or, the molar ratio of Fe3O4 to cerium salt is 1:(2-20).

8. The method for preparing an iron oxide-cerium oxide composite material according to claim 1, characterized in that: In step S6, the ratio of ultrapure water to ethanol mixed solvent is (1-5):

1.

9. An iron oxide-cerium oxide composite material, characterized in that: The composite material is prepared by the method for preparing an iron oxide-cerium oxide composite material as described in any one of claims 1 to 8.

10. Use of the iron oxide-cerium oxide composite material as claimed in claim 9 as a catalyst in a lithium-sulfur battery.

Citation Information

Patent Citations

  • Preparation method of core-shell structure Fe2O3-CeO2 / (Al@C) heat accumulation type oxygen carrier

    CN109054755A

  • Core-shell structure composite iron cerium oxide dearsenification adsorbent, and preparation method and applications thereof

    CN110327874A

  • Composite nitrogen-doped carbon catalyst as well as preparation method and application thereof

    CN116764665A

  • Mesoporous silica wrapped nanoparticle composite material, preparation method thereof, and use thereof

    US20220315440A1